Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

"What value of $b$ and $c$ for the curve $y = x^3 + bx^2 + cx$ give the tangent equation $y = 3x - 4$ in the point $(1, -1)$?"

This is what I do:

The derivative of the function is $3x^2 + 2bx + c$

In the point where $x = 1$, it becomes $3 + 2b + c$. Since the tangent equation is $3x - 4$, $3 + 2b + c = 3$. This means that $2b = -c$.

The answer in the book says that $c = -4$, and $b = 2$. However, shouldn't any value that conforms to $2b = -c$ work? I mean, they all give the slope of 3.

share|improve this question

4 Answers 4

up vote 0 down vote accepted

The question asks you to verify the equation of a tangent line to a given curve at a given point. That point must lie on the curve! You need $x=1$ and $y=-1$ to be a solution to the equation $y=x^3+bx^2+c$, i.e. you need $-1=1+b+c$ or equivalently: $b+c=-2$.

You can then do what you did and find the derivative and get the condition that $2b=-c$.

Solving the equation $b+c=-2$ and $2b=-c$ simultaneously gives $b=2$ and $c=-4$ as the book says.

share|improve this answer

You have to also make the original function pass through the point $(1,-1)$. That gives the equation

$$-1 = 1 + b + c,$$

which implies $b+c = -2$. Given $c = -2b$, as you have shown, this implies $-2 = b+c = b-2b = -b$, so indeed $b = 2$ and hence $c = -4$.

share|improve this answer
    
How does a function pass through at point? –  Fly by Night Mar 14 '13 at 19:57
    
@FlybyNight The original equation $y=x^3+bx^2+cx$ must admit $(x,y) = (1,-1)$ as a valid solution. –  gt6989b Mar 14 '13 at 20:01
    
You mean to say "the graph of the function". And even so, you can't make the graph of a function do anything; it goes where it goes. –  Fly by Night Mar 14 '13 at 20:03

$c = -10, b = 5$ fulfills $2b = -c$, but $(1,-1)$ is not a solution to $y = x^3 + 5x^2 - 10x$

Remember, the line and the curve still have to meet at $(1, -1)$

share|improve this answer

you need to use the fact that $y=-1$ which means that $1 + b + c = -1$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.